DNA methylation analysis of Sox2 regulatory regions SRR1 and SRR2 in undifferentiated and differentiated mouse embryonic stem cells - Batool, Sajida (2013)
One hallmark of embryonic stem cells (ES) is their ability to renew themselves indefinitely and still retain the potential to develop into any specialized cell type once triggered by specific exogenous signals. This very versatile nature has made them an attractive model to study developmental events occurring during embryogenesis and also to employ them for regenerative medicine. The idea to exploit their developmental potential for intended therapeutic applications requires a detailed knowledge of the molecular regulation of differentiation. Thus pluripotent embryonic stem cells can be employed to investigate the molecular framework regulating pluripotency. The major aim of this research endeavour is to explore the role of DNA methylation in regulation of endogenous Sox2 transcription factor in context of mouse ES cells following their transition from the pluripotent to a differentiated state. An insight into molecular regulatory mechanisms will shed light on developmental programming and also aid in refining of methodologies for differentiation and nuclear reprogramming increasing their chances of success and efficiency.